2008
DOI: 10.1523/jneurosci.5277-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Nucleus Accumbens Shell Attenuates Cocaine Priming-Induced Reinstatement of Drug Seeking in Rats: Figure 1.

Abstract: Increasing evidence suggests that deep brain stimulation (DBS), which is currently being used as a therapy for neurological diseases, may be effective in the treatment of psychiatric disorders as well. Here, we examined the influence of DBS of the nucleus accumbens shell on cocaine priming-induced reinstatement of drug seeking, an animal model of relapse. Rats were allowed to self-administer cocaine (0.25 mg, i.v.) 2 h daily for 21 d and then cocaine-seeking behavior was extinguished by replacing cocaine with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 40 publications
10
136
0
2
Order By: Relevance
“…So far, no lesion or DBS studies within a single brain structure have reported such an opposite dissociation. Although DBS applied at a fixed intensity for all animals in the nucleus accumbens shell has been recently reported to diminish cocaine-seeking behavior in a reinstatement experiment, there was no increase on food seeking (27). Consistent with a possible dissociation between natural reward and drugs of abuse, specific subpopulations of neurons in the nucleus accumbens have been proposed to encode either cocaine or sucrose reward (28).…”
Section: Discussionmentioning
confidence: 96%
“…So far, no lesion or DBS studies within a single brain structure have reported such an opposite dissociation. Although DBS applied at a fixed intensity for all animals in the nucleus accumbens shell has been recently reported to diminish cocaine-seeking behavior in a reinstatement experiment, there was no increase on food seeking (27). Consistent with a possible dissociation between natural reward and drugs of abuse, specific subpopulations of neurons in the nucleus accumbens have been proposed to encode either cocaine or sucrose reward (28).…”
Section: Discussionmentioning
confidence: 96%
“…Animal studies showed no effect on drugrelated behaviors after stimulation of the dorsal striatum 193 and lateral hypothalamus. 114 Lateral habenula stimulation was effective in controlling drug consumption but also decreased food consumption, which was considered an undesirable side effect.…”
Section: Addictionmentioning
confidence: 95%
“…100 Several preclinical studies in rats have investigated the effect of high-frequency DBS on ethanol consumption and cocaine/narcotic-seeking behavior. 15,79,92,165,193 These studies showed a significant reduction in drugseeking behaviors following DBS.…”
Section: Addictionmentioning
confidence: 96%
“…The translation of the results in human medicine is possible, if the models are valid. Some recent studies proved model validity in OCD (Mundt et al, 2009;Klavier et al, 2009;Klavier, Winter & Joel, 2011;Djodari-Irani et al, 2010;, depression , and substance dependency (Vassoler et al, 2008;Rouaud et al, 2010) (for overview see Winter, Harnack & Kupsch, 2010).…”
Section: Fourth Approach: Translational Researchmentioning
confidence: 99%